PENGEMBANGAN MEDIA PEMBELAJARAN E-COMIC BERBASIS MODEL PROBLEM BASED LEARNING MATERI CERITA TENTANG DAERAHKU DI KELAS IV SDN 04 KOTO BARU - Moh. Rosyid mahmudi; Estuhono Estuhono; Aini Septianingsih (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Education is the process of changing the attitudes and behavior of a person or group in an effort to mature humans. This research uses the type of research and development (research and development). The ADDIE development model has five stages, namely: Analyze, Design, Development, Implementation, Evaluation. The types of data taken from the development of E-comic media are qualitative and quantitative data. The instrument used in this study, validation of the E-comic media, the practicality instrument of the E-comic media, the effectiveness instrument of the E-comic media. data collection techniques used are interviews, observations, and questionnaires (questionnaire). Analysis of data in research using analysis of validity, practicality and effectiveness. From the results of validation, practicality and effectiveness, the following results can be obtained: The validity of the E-comic learning media assessed by validators, totaling 3 people, obtained a percentage of 0,885% in a valid category, E-comic learning media is feasible to use and in accordance with the provisions of SDN 04 Koto Baru. Practicality is assessed from the teacher response questionnaire and student response questionnaire. The teacher response questionnaire was 86% in the very practical category, the student response questionnaire was 90% in the very practical category, so based on this analysis it was concluded that pop-up book media was very practical. Furthermore, the effectiveness assessed from the results of the Reading Ability test obtained a percentage of 90% in the very effective category.